The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.5194/acp-20-487-2020
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis and oxidation by OH radicals of two carbonyl nitrates: 4-nitrooxy-2-butanone and 5-nitrooxy-2-pentanone

Abstract: Abstract. Multifunctional organic nitrates, including carbonyl nitrates, are important species formed in NOx-rich atmospheres by the degradation of volatile organic compounds (VOCs). These compounds have been shown to play a key role in the transport of reactive nitrogen and, consequently, in the ozone budget; they are also known to be important components of the total organic aerosol. However, very little is known about their reactivity in both the gas and condensed phases. Following a previous study that we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(42 citation statements)
references
References 31 publications
6
36
0
Order By: Relevance
“…It is also expected that organic nitrates adsorb on the stainlesssteel walls. Indeed, the loss rates of several multifunctional organic nitrates (in particular carbonyl nitrates) have been observed in previous studies (Suarez-Bertoa et al, 2012;Picquet-Varrault et al, 2020) and were found to range between 0.5 and 2 × 10 −5 s −1 . However, as yields of organic nitrates in the gas phase were calculated during a relatively short period (less than 1 h), these wall losses are expected to be low (less than 10 %), and this is confirmed by the good linearity of the plots.…”
Section: Organic Nitrate Yieldssupporting
confidence: 57%
See 2 more Smart Citations
“…It is also expected that organic nitrates adsorb on the stainlesssteel walls. Indeed, the loss rates of several multifunctional organic nitrates (in particular carbonyl nitrates) have been observed in previous studies (Suarez-Bertoa et al, 2012;Picquet-Varrault et al, 2020) and were found to range between 0.5 and 2 × 10 −5 s −1 . However, as yields of organic nitrates in the gas phase were calculated during a relatively short period (less than 1 h), these wall losses are expected to be low (less than 10 %), and this is confirmed by the good linearity of the plots.…”
Section: Organic Nitrate Yieldssupporting
confidence: 57%
“…Since the early 1980s and the discovery of the nitrate radical (NO 3 ) in the nocturnal troposphere (Noxon et al, 1980;Platt et al, 1980) and stratosphere (Naudet et al, 1981;Noxon et al, 1978), nighttime chemistry has been known to be active. NO 3 is mainly formed by the reaction of nitrogen dioxide (NO 2 ) with ozone and has two very efficient sinks during the day, its photolysis and its reaction with NO (Brown and Stutz, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the developed SAR to predict the kOH rate constants of other atmospherically relevant organic nitrates to evaluate if the aqueous-phase •OH-oxidation has a significant role on their atmospheric lifetimes. Some of the evaluated organic nitrates have been detected in field campaigns (Beaver et al, 2012;Li et al, 2018); they are expected products from isoprene or monoterpenes photooxidation (Lee et al, 2014); or they are small polyfunctional nitrates that may be formed by the fragmentation of terpene nitrates or by the oxidation of alkyl nitrates (Picquet-Varrault et al, 2020;Treves and Rudich, 2003). Selecting organic nitrates potentially relevant to atmospheric chemistry, as well as those mentioned in the literature, we listed 49 compounds that were divided into 7 categories depending on their functionalization and chemical structure: 6 alkyl nitrates, 7 hydroxy nitrates, 7 ketonitrates, 5 aldehyde nitrates, 5 nitrooxy carboxylic acids, 7 other polyfunctional nitrates containing more than one oxygenated group, and 12 terpene nitrates corresponding to highly oxidized organic nitrates formed by the oxidation of terpenes, such as α-and β-pinene, limonene and myrcene.…”
Section: Atmospheric Implicationsmentioning
confidence: 99%
“…The gas-phase chemistry of organic nitrates has been studied through kinetic experiments focusing on their •OH-oxidation (Bedjanian et al, 2018;Picquet-Varrault et al, 2020;Treves and Rudich, 2003;Wängberg et al, 1996;Zhu et al, 1991) and direct photolysis (Clemitshaw et al, 1997;Picquet-Varrault et al, 2020;Suarez-Bertoa et al, 2012). These experiments provide data for different types of organic nitrates, including alkyl nitrates, ketonitrates, hydroxy nitrates, dinitrates, cyclonitrates and alkene nitrates, and provide knowledge on their gas-phase atmospheric fate.…”
Section: Introductionmentioning
confidence: 99%